PROFESSIONAL ORIENTATION AND ENROLLMENT OF SECONDARY SCHOOL GRADUATES AT THE UNIVERSITY - Sead Rešić; Hariz Agić (Human Research in Rehabilitation, 2013)
Creating an environment for more efficient university education is closely related to effective planning, conducting and continuous improvement of realization of professional orientation program for students in elementary and secondary schools. The lack of personal vision of professional development for students in elementary and secondary schools, even several months before applying at university is defeating for the inputs in the process of higher education. The aim of this research was to evaluate the opinion of examinees – secondary school graduates (comprehensive schools, technical schools and those affine) – on issues regarding their intentions and decisions about continuing education, and to determine how these decisions were made. The analysis of gathered data revealed that the continuing of their education is not in sufficient accordance with their choice of secondary school. The results showed that the choice of current school and professional orientation program for students in elementary and secondary schools is not in accordance with their decision-making regarding continuing education at the university